1999
DOI: 10.1021/om9903947
|View full text |Cite
|
Sign up to set email alerts
|

C2-Symmetrical Diazabutadiene Complexes of Platinum(II) and the Promotion of Cationic Polymerization

Abstract: The synthesis, characterization, and reaction chemistry of a cationic Pt(II) solvento complex (2) are described. The complex demonstrates the unprecedented ability to promote polymerization of the electron-rich olefins ethyl vinyl ether (EVE), N-vinylcarbazole (NVC), and 2,3-dihydrofuran (DHF) via cationic initiation and subsequent propagation of the carbocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
19
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 36 publications
7
19
1
Order By: Relevance
“…The dyad and triad tacticity of poly(vinyl ether) were determined by using 13 C NMR spectra recorded on a Varian Unity Plus 300 spectrometer in CDCl 3 at 25 8C, using tetramethylsilane as the internal reference. which are quite similar to those reported by Eisenberg and co-workers when utilizing of diimine-platinum(II) complex as a catalyst [10] and to those by Liu and co-workers utilizing a cationic palladium diimine complex. [13] In addition, the molecular weight values of the poly(vinyl ether)s achieved by Ni II catalysts prepared modifying the bulkiness of the ligand were different from those of polyethylenes with the same catalysts.…”
Section: Characterization Of Polymerssupporting
confidence: 88%
See 1 more Smart Citation
“…The dyad and triad tacticity of poly(vinyl ether) were determined by using 13 C NMR spectra recorded on a Varian Unity Plus 300 spectrometer in CDCl 3 at 25 8C, using tetramethylsilane as the internal reference. which are quite similar to those reported by Eisenberg and co-workers when utilizing of diimine-platinum(II) complex as a catalyst [10] and to those by Liu and co-workers utilizing a cationic palladium diimine complex. [13] In addition, the molecular weight values of the poly(vinyl ether)s achieved by Ni II catalysts prepared modifying the bulkiness of the ligand were different from those of polyethylenes with the same catalysts.…”
Section: Characterization Of Polymerssupporting
confidence: 88%
“…[1,2] Vinyl ether monomers containing electrondonating groups can be cationically polymerized by utilizing Lewis acid due to the resonance stabilization of carbocations by lone pair electrons on the oxygen. [3][4][5][6] Some studies have been reported to control the stereoregularity in vinyl ether polymerization by using special Ziegler-type catalysts, [7,8] metallocene catalysts, [9][10][11][12] and postmetallocene catalysts. [12] Even if the cationic late transition metal complexes are known to be remarkably functional group tolerant, [1,2] late transition metal complexes are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The two acetonitrile moieties are practically linear, as expected, and the bond lengths and angles fall in the range usually found for this ligand coordinated to Pt. [24][25][26][27][28] The molecular skeleton C 2 PtP 2 PtN 2 is not planar. The angle between the perpendicular lines to the best square planes formed by the Pt atoms and the atoms directly bonded to them is 33.94(4)°.…”
Section: Resultsmentioning
confidence: 99%
“…ORTEP view of the cation in compound 3s[BF 4 ]; ellipsoids as inFigure 1pared with the PtϪNCMe bond length, 1.955(4) Å , found in the cation [Pt(Me)(MeCN)(Ar 2 DAB)] ϩ[19] (Ar 2 DAB ϭ diaryldiazabutadiene). It is interesting also to observe that the N2ϪPtϪN3 angle, 103.7(1)°, is very similar to the N2ϪPtϪCl angle, 103.1(1)°, found in 3a, thus confirming the hypothesis that it is a result of the bulkiness of the ethyl substituent on the bipyridine ligand.…”
mentioning
confidence: 99%